EXPLORING ETHICAL AND CULTURAL FACTORS INFLUENCING PARTICIPATION IN SNOWBALL SAMPLING STUDIES - Dewin Arona Sikalumbi; Jonas Simbeye; Beatrice Chirwa (International Journal of Innovative Technologies in Social Science, 2025)
This scoping review explores the ethical and cultural factors affecting participation in online snowball sampling studies among hard-to-reach populations. The guiding questions are: (1) What ethical factors influence participation in these studies? (2) What cultural factors affect potential participants’ decisions? Snowball sampling relies on current participants recruiting future ones, a method increasingly utilized by qualitative researchers in social and health sciences. While previous reviews address ethical challenges and recommendations, such as concerns about data turnover and reputational risk, the ethical and cultural influences on participation in such online research are less understood. This study employs a scoping review methodology to identify, chart, and summarize the relevant literature. It adheres to scoping review methods while ensuring rigor and flexibility. A systematic search of online bibliographic databases yielded a dataset of articles, which were screened based on inclusion and exclusion criteria, followed by full-text screening. Data extracted from the selected articles, including publication details and topics—are thematically organized. This research only considers academic articles published in English and excludes conference abstracts, reports, books, government documents, dissertations, presentations, or grant applications.